Pengaruh Tradisi Membaca Al-Qur’an Terhadap Prestasi Belajar Siswa di MA Al-Hidayah - Siti Rosmayati; Arman Maulana; Boy Arief Rochman (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2020)
Reading al-quran is something that lives full of serenity. As Muhammad SAW in his revelation is instructed to read the Koran and through reading Allah commands something or knowledge that is unknown. Al-qur'an reading activities carried out by students of MA Al-Hidayah class X, the level of learning achievement of Islamic Religious Education students of class X, and there is no effect of the effect of reading the al-qur'an on student achievement in grade X quantitative research approach with simple linear regression analysis. The population in this study were all class X students at Al-Hidayah Private Madrasah Aliyah which correspond to 212 students. So the sampling using cluster sampling technique by taking class X 80 students. The results of this data analysis are as follows: the variable of students' reading habits of the Al-Qur'an on the learning achievement of PAI in cognitive and affective aspects has a significance value of 0.001 and 0.011. Because the probability values of 0.002 and 0.025 are smaller than 0.05, the alternative hypothesis (Ha) is accepted. And the analysis for the variable of the habit of reading the Koran on the students' psychomotor aspects of Islamic Education learning achievement obtained a significance value of 0.001. Because the probability (0.001) is smaller than 0.05, the alternative hypothesis (Ha) is accepted.Keywords: habit of reading al-quran, learning achievement Abstrak Membaca Al-Qur’an merupakan sesuatu yang menjadikan hidup penuh dengan ketenangan. Sebagaimana nabi Muhammad SAW dalam wahyunya diperintahkan membaca al-Quran dan melalui membaca Allah mengajarkan manusia sesuatu atau pengetahuan yang tidak diketahui. Adapun kebiasaan membaca Al-Qur’an yang dilakukan oleh siswa MA Al-Hidayah kelas X, tingkat prestasi belajar Pendidikan Agama Islam siswa kelas X, dan ada tidaknya pengaruh kebiasaan membaca Al-Qur’an terhadap prestasi belajar siswa kelas X. Dalam penelitian ini menggunakan pendekatan penelitian kuantitatif dengan analisis Regresi Linear Sederhana. Populasi dalam penelitian ini adalah seluruh siswa kelas X di Madrasah Aliyah Swasta Al-Hidayah yang berjumlah 212 siswa. Maka dilakukan pengambilan sample penelitian menggunakan terknik cluster sampling dengan mengambil siswa kelas X 80 siswa. Hasil analisis data ini adalah sebagai berikut: variabel kebiasaan membaca Al-Qur’an siswa terhadap prestasi belajar PAI aspek kognitif dan afektif di peroleh nilai signifikansi 0,001 dan 0,011. Oleh karena nilai probabilitas 0,002 dan 0,025 lebih kecil dari 0,05 maka hipotesis alternatif (Ha) diterima. Dan analisis untuk variable kebiasaan membaca Al- Qur’an terhadap prestasi belajar PAI siswa aspek psikomotorik diperoleh nilai signifikansi 0,001. Oleh karena probabilitas (0,001) lebih kecil dari 0,05 maka hipotesis alternatif (Ha) diterima. Kata kunci: kebiasaan membaca Al-Qur’an, prestasi belajar